Quantifying the amount of greater brain ischemia protection time with pre-hospital vs. in-hospital neuroprotective agent start - Matossian, Vartan; Starkman, Sidney; Sanossian, Nerses; Stratton, Samuel; Eckstein, Marc; Conwit, Robin; Liebeskind, David S.; Sharma, Latisha; Tenser, May-Kim; Saver, Jeffrey L. (Frontiers in Neurology, 2022)
The objective of this study is to quantify the increase in brain-under-protection time that may be achieved with pre-hospital compared with the post-arrival start of neuroprotective therapy among patients undergoing endovascular thrombectomy. In order to do this, a comparative analysis was performed of two randomized trials of neuroprotective agents: (1) pre-hospital strategy: Field administration of stroke therapy-magnesium (FAST–MAG) Trial; (2) in-hospital strategy: Efficacy and safety of nerinetide for the treatment of acute ischemic stroke (ESCAPE-NA1) Trial. In the FAST-MAG trial, among 1,041 acute ischemic stroke patients, 44 were treated with endovascular reperfusion therapy (ERT), including 32 treated with both intravenous thrombolysis and ERT and 12 treated with ERT alone. In the ESCAPE-NA1 trial, among 1,105 acute ischemic stroke patients, 659 were treated with both intravenous thrombolysis and ERT, and 446 were treated with ERT alone. The start of the neuroprotective agent was sooner after onset with pre-hospital vs. in-hospital start: 45 m (IQR 38–56) vs. 122 m. The neuroprotective agent in FAST–MAG was started 8 min prior to ED arrival compared with 64 min after arrival in ESCAPE–NA1. Projecting modern endovascular workflows to FAST–MAG, the total time of “brain under protection” (neuroprotective agent start to reperfusion) was greater with pre-hospital than in-hospital start: 94 m (IQR 90–98) vs. 22 m. Initiating a neuroprotective agent in the pre-hospital setting enables a faster treatment start, yielding 72 min additional brain protection time for patients with acute ischemic stroke. These findings provide support for the increased performance of ambulance-based, pre-hospital treatment trials in the development of neuroprotective stroke therapies.